Special Analysis of Migrant Education Even Start Data. Even Start Information System - Tao, Fumiyo; Arriola, Christine; Fu Associates, Ltd. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
This report analyzes data submitted by 11 of 14 state Migrant Education Even Start (MEES) projects operating in 1994-95. These projects provide migrant families with an integrated program of early childhood education, adult education, and parenting education. The data were drawn from the Even Start Information System (ESIS), which collected 1994-95 data on 476 Even Start projects nationwide. The 11 reporting MEES projects served 20-150 families, received funding primarily through local educational agencies, filled various local unmet needs for services, had average combined federal and local funding of $330,688, and had an average of 7 instructors and 16 total staff. Among instructors, 41 percent had a bachelor's degree or higher, and half had 6 or more years of relevant work experience. Project staff reported on inservice training received, barriers to program implementation, technical assistance needs, service delivery schedules for various educational activities, types of parenting education activities and parent-child activities offered, content of adult education services, integration of core MEES services, collaboration with other agencies, and family needs for support services. Participants were primarily Hispanic two-parent families with an average of four children under age 16. Other family characteristics reported include length of U.S. residence, parent educational background, parent employment status, family income, and English language proficiency. Data on participation outcomes include home visits made, extent of parent and child participation in various services, support services received, prevalence of children with special needs, and retention and successful completion of MEES services. Many data tables are included. (SV)
Sponsoring Agency: Department of Education, Washington, DC. Planning and Evaluation Service.
Contract Number: EA94068001.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Delivery Systems; English (Second Language); Family English Literacy; Family Programs; Literacy Education; Migrant Adult Education; Migrant Education; Migrant Programs; Participant Characteristics; Preschool Education; Even Start; Program Characteristics; Numerical/Quantitative Data; Reports, Research